Interrogative Construction in Javanese: X-Bar Theory Analysis - Dewi Nurmala; Mulyadi Mulyadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This research aims to determine the elements forming the interrogative sentences in interrogative construction of Javanese language using X-Bar theory. Interrogative construction in a sentence requires yes/no answers or new information is required. The object of the research is interrogative construction in Javanese. The data obtained are interrogative sentences in Javanese. The method used is descriptive qualitative. Data analysis was carried out by condensing data, displaying data and conclusions. From the results of the study it was found that the interrogative construction in Javanese can be concluded that the position of the functional category of interrogative sentence lies in the position of the specifier, complement, and complement. Direct question words with yes/no answers and echo questions occupy positions as complements. Direct question words that require answers such as question words, ing endi (where), and kepriye (how) occupy positions as complements. Meanwhile, a direct question words that require answers, such as the question words sapa (who) and kapan (when) occupy a position as a specifier.